Efficacy of drainage trenches to stabilise deep slow landslides in clay slopes. Issue 1 (20th January 2016) - Cotecchia, F.; Lollino, P.; Petti, R.
Abstract : The paper reports the results of a research aiming at the definition of innovative strategies to mitigate the risk generated by deep landsliding due to the slope-atmosphere interaction. The aim stems from the recognition of the connection between the accelerations of deep slow landslides and the seasonal fluctuations of the piezometric heads found to occur down to large depths in slopes, effect of seasonal cumulated rainfall infiltration, as verified in previous research studies for fissured clay slopes of the Italian southern Apennines. Given this slope behavior, the effects as stabilizing measure of systems of drainage trenches, from medium depth to deep, have been verified through the combination of finite element modeling of seepage and limit equilibrium analyses. The model results show that the trench system generates a 'group effect' on the piezometric heads at large depth, due to which the maximum drop in piezometric head occurs along the portion of maximum depth of spoon-shaped slip surfaces underlying the trench system. Hence, the reduction in piezometric head generated by the trench system makes such system an effective mitigation measure for deep landsliding. In the paper, the stabilizing effect of the trench system is also verified through its modeling for a deep landslide case history.